The Use of Media to Build Geometry for Embedding The Adding of Fractions Concept - Nanik Ulfa (Jurnal Pendidikan Sains, 2013)
Penggunaan Media Bangun Geometri untuk Menanamkan Konsep Penjumlahan Pecahan Abstract: Understanding the concept is very important in the study of mathematics. To instill understanding of the concept to students who are still in the stage of concrete thinking which does not require the assistance of foreign media for students. In this study used media is media geometry field. The use of media in this study is expected to provide a fun learning situation and invite the students actively involved in learning. Learning is done in three stages: (1) the initial stage, ie the stage to check the prerequisite knowledge of students, (2) the core stage, in this stage the media students to manipulate geometry in accordance with the guidelines in worksheets that have been prepared by the researcher, (3) concluding phase, teachers and students collectively at the conclusion of the study that has been done. From this study showed that the average percentage of student activity keterlaksanaan obtained for 95.8% and 90.4% of teachers' activities. Based on the results of the final test showed that action learning completeness reached 89% of the 19 students who took the tests achieve mastery. Key Words: media, geometry, concept, the sum of fractions Abstrak: Pemahaman konsep sangat penting dalam mempelajari matematika. Untuk menanamkan pemahaman konsep kepada siswa yang masih dalam taraf berfikir konkret diperlukan bantuan media yang tidak asing bagi siswa. Dalam penelitian ini media yang digunakan adalah media bangun geo-metri bidang. Penggunaan media dalam penelitian ini diharapkan dapat memberi situasi pembelajaran yang menyenangkan dan mengajak siswa terlibat aktif dalam pembelajaran. Pembelajaran dilakukan dengan tiga tahap, yaitu (1) tahap awal, yaitu tahap untuk mengecek pengetahuan prasyarat siswa, (2) tahap inti, dalam tahap ini siswa memanipulasi media bangun geometri sesuai dengan panduan dalam LKS yang telah disusun oleh peneliti, (3) tahap penutup, guru dan siswa bersama-sama meng-ambil kesimpulan dari pembelajaran yang telah dilakukan. Dari penelitian ini diperoleh hasil yaitu ra-ta-rata persentase keterlaksanaan aktivitas siswa diperoleh sebesar 95,8% dan kegiatan guru sebesar 90,4%. Berdasarkan hasil tes akhir tindakan diperoleh bahwa ketuntasan belajar mencapai 89% dari 19 siswa yang mengikuti tes mencapai ketuntasan.Kata kunci: media, bangun geometri, konsep, penjumlahan pecahan